Sublingual dermoid cyst: Case report and a review of the clinical, radiological and histological aspects of this rare condition. (2nd November 2017) - Lee, M.H.A.; Lee, C.S.; Sim, C.Q.X.; Nagadia, R.
Abstract: Dermoid cyst of the floor of the mouth is a rare condition. It usually present as a non‐tender, slow growing swelling at the sublingual region. The clinical presentation may be similar to several other conditions. We report a case of an adolescent female who present at our institution with a sublingual swelling which was initially diagnosed as a plunging ranula. The lesion was excised together with the sublingual gland and then diagnosed histologically as a dermoid cyst. Post‐operative healing was uneventful. This report will also review the current literature on the clinical, radiological and histological aspect of the dermoid cyst to give the reader a greater understanding of this rare condition.